Transformational Leadership and Knowledge Transfer Enhance MSME Employees’ Performance - Joeliaty Joeliaty; Sri Djatnika Sya’diah; Umi Kaltum (Cita Konsultindo Research Center, 2024)
Population growth presents significant market potential for Micro and Small Medium Enterprises (MSMEs), intensifying competition. This study aims to elucidate the impact of leadership and knowledge transfer on MSME performance, addressing the gap in academic literature. Employing a qualitative approach supported by quantitative data, non-probabilistic descriptive analysis was conducted to explore grounded theory. MSME actors transfer knowledge through traditional methods and utilize platforms like WhatsApp to enhance employee performance. Effective leadership practices, including employee inclusion and guidance, were observed. Integrating leadership styles and knowledge transfer can optimize SME employee performance, facilitating business growth and competitiveness. This research uniquely integrates leadership styles and knowledge transfer to enhance employee performance in SMEs, offering a concise perspective on their synergistic impact.